Do Americans Really Support Black Athletes Who Kneel During the National Anthem? Estimating the True Prevalence and Strength of Sensitive Racial Attitudes in the Context of Sport. (December 2022) - Mueller, Lisa
Professional athletes in the United States have protested racism in various ways for decades. Kneeling during the national anthem became a prominent form of such activism, ever since American football player Colin Kaepernick popularized the practice in 2016. "Anthem protests" gained renewed attention after the police killing of George Floyd and nationwide unrest in the summer of 2020. This article explores whether public approval of those protests was weaker than scholars and journalists suggested, because survey respondents were reluctant to admit that they considered the protesters disrespectful. A list experiment confirms hidden opposition to anthem protests, especially among people of color, who may feel heightened pressure to support racialized protesters. A second experiment reveals that social desirability bias persists even after respondents hear reassurance that nobody will judge their views. These findings indicate that mainstream surveys misrepresent attitudes toward contemporary racial issues, and that anthem protests have yet to gain wide acceptance in the general U.S. population.